1996
DOI: 10.1159/000203858
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative ELISA for Measuring Red Cell-Bound Immunoglobulins

Abstract: An ELISA was developed for quantitating red-cell-bound IgG and IgA and its feasibility assessed on 50 blood donations and 32 clinical specimens with raised cell-bound IgG. Test and quality control samples and immunoglobulin standards (in red-cell lysate buffer) were assayed together. Calibration curves were derived from the standards, test values being read off and related to cell count. The working range was around 5-70 ng/ml, the upper limit being indefinitely extendable by dilution with lysate buffer. Range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…10 That study reported a median of < 29 molecules per RBC, which is comparable to the amount quantitated by our assay. 10 There was considerable variation in the number of IgG, IgA, and IgM molecules per RBC in patients with AIHA, demonstrating the ability of the assay to measure widely different degrees of sensitization in clinical samples. The results are comparable with previous studies where the reported ranges in patients with AIHA were from 230 to about 30,000 IgG molecules, from 20 to 168 IgM molecules, and from < 29 to 4500 IgA molecules per RBC.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…10 That study reported a median of < 29 molecules per RBC, which is comparable to the amount quantitated by our assay. 10 There was considerable variation in the number of IgG, IgA, and IgM molecules per RBC in patients with AIHA, demonstrating the ability of the assay to measure widely different degrees of sensitization in clinical samples. The results are comparable with previous studies where the reported ranges in patients with AIHA were from 230 to about 30,000 IgG molecules, from 20 to 168 IgM molecules, and from < 29 to 4500 IgA molecules per RBC.…”
supporting
confidence: 76%
“…Other methods gave similar results for IgG and IgM. 4,5,[8][9][10] There has been only one previous report of the number of RBC-associated IgA molecules on normal human RBCs. 10 That study reported a median of < 29 molecules per RBC, which is comparable to the amount quantitated by our assay.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…39 The method is similar to that used by others. 39,40 After measuring RBC concentration in samples tested, we calculated the extent of RBC sensitization molecules of IgG, IgA, IgM, C1q, and C3 per RBC.…”
Section: Methodsmentioning
confidence: 99%